Automatic mapping tasks to cores - Evaluating AMTHA algorithm in multicore architectures - de Giusti, Laura Cristina (2010)
The AMTHA (Automatic Mapping Task on Heterogeneous Architectures) algorithm for task-to-processors assignment and the MPAHA (Model of Parallel Algorithms on HeterogeneousArchitectures) model are presented.The use of AMTHA is analyzed for multicore processor-based architectures, considering the communication model among processes in use.The results obtained in the tests carried out are presented, comparing the real execution times on multicores of a set of synthetic applications with the predictions obtained with AMTHA.Finally current lines of research are presented, focusing on clusters of multicores and hybrid programming paradigms.